Crafting a policy statement: Some observations. Issue 3 (23rd July 2019) - Jodock, Darrell
Abstract: In 2016, a task force appointed by the Evangelical Lutheran Church in America began drafting a policy statement which in 2018 appeared with the title "A Declaration of Inter‐Religious Commitment." This article explains the production of that document and explores its main themes. The document appeals to vocation—that is, the calling to serve one's neighbor and community—as its framework. It encourages engagement, resisting stereotypes, cooperation for the common good, and standing up for those who are harassed or mistreated. It goes on to explore the relationship between evangelism and inter‐religious understanding, affirming both the Great Commandment and the Great Commission.